Pengaruh Pelatihan Gaya Belajar terhadap Peningkatan Indeks Prestasi Mahasiswa - Mulyono, Wastu Adi; Purwandari, Haryatiningsih; Permana, Ryan Hara (Jurusan Keperawatan FIKES UNSOED, 2007)
This research aimed to understand effect of learning style training toward student’s grade, especially to describe student’s grade before and after training, learning style characteristics to test the effect of learning style training toward increasing of student’s grade . This semi experiment research was designed in pre and post test design and pair t test data analysis. Thirty one students which got grade below 2.5 participated. Learning style training were trained to them for 4 hours along. Student’s grade before and after training were collected and compared. Learning modalities were measured by DePorter Instruments. Research resulted in increasing mean of student grade about 0.58 (SD 0.44) after the training. Most of them had Visual Modality (54.8%) and had Unsequential Abstract Thinking Character (64.5). Pair t-test analyses showed that t=7.26, p value 0.00, α=0.05 one tailed, Learning Style Training influenced student’s grade statistically significant.